From Rapunzel to Tangled and beyond: Multimedia practices in the language and literature classroom - De Cunto, Martha; García, María Laura (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
This is a classroom account of a project which consisted of a series of multimedia lessons that have been carried out with 11- and 12-year-old Language and Literature students in a bilingual school in the City of Buenos Aires with the aim of working with multimodal texts simultaneously. The lessons pivoted around the main characteristics of fairy tales as a literary genre and the identification of those elements in the film Tangled (2010); the relationship between the written version of the fairy tale Rapunzel by the Grimm Brothers and the film Tangled (2010), including the exploration of the idea of fracture; and a very general introduction to the concept of remediation defined by Bolter and Grusin (2000, p. 45) as “the representation of one medium in another.”